1984
DOI: 10.1161/01.str.15.4.627
|View full text |Cite
|
Sign up to set email alerts
|

A double blind trial of naloxone in the treatment of acute stroke.

Abstract: Naloxone has been reported to have potential benefit in the treatment of stroke. We evaluated the effect of naloxone in a double-blind trial conducted with 15 stroke patients whose deficits ranged from 8 to 60 hours in duration. All but one patient sustained a cerebral infarction. Neurologic function was assessed before and five minutes after each of two injections given to each patient in a double-blind fashion. The injections consisted of naloxone (0.4 mg in 3 patients and 4.0 mg in 12 patients) and saline. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…This high dose of naloxone has proved less effective than a dose of 2 mg/kg following experimental shock in the rat. 31 Similarly, we recently demonstrated that naloxone doses of 10 mg/kg Fallis et al 35 1983…”
Section: Opiate Antagonistsmentioning
confidence: 79%
See 1 more Smart Citation
“…This high dose of naloxone has proved less effective than a dose of 2 mg/kg following experimental shock in the rat. 31 Similarly, we recently demonstrated that naloxone doses of 10 mg/kg Fallis et al 35 1983…”
Section: Opiate Antagonistsmentioning
confidence: 79%
“…The neurological deficit returned within one hour of drug administration in two of the three patients showing some response. Finally, Fallis et al 35 evaluated naloxone in a double-blind trial with 15 patients (14 with cerebral infarction) and found no beneficial effects with regard to neurological function. Patients were treated between 8 and 60 hours after onset of symptoms with a dose of 0.4 to 4.0 mg.…”
mentioning
confidence: 99%
“…For potential therapeutic purposes, naloxone has been tested in animal models and clinical trials to treat a wide range of disease conditions, including drug abuse, alcohol addiction, eating disorder, spinal cord injury, shock, and cerebral and cardiac ischemia (Hosobuchi et al, 1982;Fallis et al, 1983;Holaday and Malcolm, 1986;de Zwaan and Mitchell, 1992;Kan et al, 1992;Ward et al, 1999;Napolitano, 2000;Seidl, 2000;Anton, 2001;Chen et al, 2001). Although the efficacy of naloxone in treating drug abuse is clearly related to its activity as an opioid antagonist, the exact mechanism of action responsible for the efficacy of naloxone in other cases remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Neurologic parameters assessed included National Institutes of Health stroke scale score, 30 level of consciousness, orientation, response to commands, visual fields, gaze, pupillary responses, sensory responses, motor function, limb coordination, plantar reflex, presence of neglect, language, and articulation. The patients' baseline, completion of loading dose, and 3 -month neurologic conditions were categorized as normal (stroke scale score of 0) or mild (1-10), moderate (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), or severe (^30) deficit.…”
Section: Methodsmentioning
confidence: 99%